2002
DOI: 10.1007/bf02412142
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and fracture of bovine dentin

Abstract: ABSTRACT-In this paper, the fatigue and fracture properties of bovine dentin are evaluated using in vitro experimental analyses. Double cantilever beam (DCB) specimens were prepared from bovine maxillary molars and subjected to zeroto-tension cyclic loads. The fatigue crack growth rate was evaluated as a function of the dentin tubule orientation using the Paris law. Wedge-loaded DCB specimens were also prepared and subjected to monotonic opening loads. Moiré interferometry was used to acquire the in-plane disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Examples are shown in Figure 6. Similar cracks in the dentin of restored teeth were reported by Arola et al [9]. The sectioned teeth were then broken along the crack and the fracture surface was examined using profilometry and power spectrum analysis.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Examples are shown in Figure 6. Similar cracks in the dentin of restored teeth were reported by Arola et al [9]. The sectioned teeth were then broken along the crack and the fracture surface was examined using profilometry and power spectrum analysis.…”
Section: Resultssupporting
confidence: 55%
“…A number of in vitro studies on cyclic crack growth in bovine [8][9][10], elephant [11,12] and human dentin [13][14][15] have been conducted in the recent past. These studies have been successful in quantifying the fatigue properties of dentin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…250 m wide) on both sides the crack boundary. 10 The nonlinear zone remained after crack extension and established the presence and contribution of permanent deformation to crack extension. Thus, the decrease in m with increasing R for fatigue loading of the bovine DCB specimens appears to have resulted from the increasing component of viscoplastic contributions to crack growth.…”
Section: Discussionmentioning
confidence: 98%
“…9 In fact, the fatigue properties of tooth tissues and dental restorative materials are just beginning to receive meaningful attention. The mechanics of fatigue crack growth and fracture in dentin was recently evaluated by Arola et al, 10 and it was found that there was a host of complex mechanisms contributing to crack extension under monotonic and cyclic loads. A complementary study by Arola and Rouland 11 identified that the average fatigue crack growth rate in bovine dentin was approximately 5E-6 mm/ cycle and dependent on the dentin tubule orientation.…”
Section: Introductionmentioning
confidence: 99%